ANALYSIS OF THE EFFECTIVENESS OF VILLAGE FUND POLICY IN ECONOMIC AND INFRASTRUCTURE DEVELOPMENT IN PALANGKA VILLAGE, SOUTH SINJAI DISTRICT, SINJAI REGENCY - Agus Sariman; Muh. Jamil (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to determine economic and infrastructure development, the effectiveness of the use of village funds in economic and infrastructure development and the impact of economic and infrastructure development on the community in Palangka Village, South Sinjai District, Sinjai Regency. The results of the study show that (1) Economic development in Palangka Village, South Sinjai District, Sinjai Regency is realized in the field of community empowerment where there is the formation of Village-Owned Enterprises and the provision of capital for cooperatives and MSMEs. Management training is facilitated for cooperatives and MSMEs. Meanwhile, infrastructure development is realized through the construction and improvement of community road access and the construction of irrigation channels for farmers; (2) The effectiveness of the use of funds in Palangka Village, South Sinjai District, Sinjai Regency in 2019 was 98.23%, in 2020 it was 99.50%, in 2021 it was 94.94%, in 2022 it was 97.84% and in 2023 it was 95.36%. From 2019 to 2023, the effectiveness of the use of funds in Palangka Village, South Sinjai District, Sinjai Regency is in the " effective" category; (3) Economic development and infrastructure development in Palangka Village, South Sinjai District, Sinjai Regency have an impact on the community. Economic development is realized through the formation of BUM Desa, the community feels helped so that this can also open up employment opportunities. The community also gets capital and opens businesses. So this can increase community income.